Spatial Equilibrium, the Theory of Rents, and the Measurement of Benefits from Public Programs - Lind, Robert C. (Quarterly Journal of Economics, 1973)
I. Introduction, 188. — II. The model, 190. — III. Benefit measurement, 194. — IV. Changes in land values and the measurement of benefits, 201. — V. Discussion and interpretation of the basic approach, 203.